Inadequacy and underreporting of study subjects’ race and ethnicity in federally funded pelvic floor research - Grimes, Cara L.; Clare, Camille A.; Meriwether, Kate V.; Husk, Katherine; Rogers, Rebecca G. (American journal of obstetrics and gynecology, 2021)
The inclusion of participants who are Black, Indigenous people of color, and participants of various ethnicities is a priority of federally sponsored research. This study aimed to describe the reporting of race and ethnicity in federally funded research published by the Eunice Kennedy Shriver National Institute of Child Health and Human Development–funded Pelvic Floor Disorders Network. Pelvic Floor Disorders Network publications were reviewed to determine whether race or ethnicity was reported. The number of participants included in each manuscript who were identified as White, Black, Asian, American Indian or Alaska Native, Native Hawaiian or Other Pacific Islander, and “other,” and the number of participants who identified as having Hispanic ethnicity were recorded. Data were analyzed by publication and by the pelvic floor disorder investigated, including urinary incontinence, pelvic organ prolapse, fecal incontinence, pregnancy-related pelvic floor disorders, and multiple pelvic floor disorders. Many publications reported on overlapping patient populations, which included primary trials and secondary analyses and studies. Data were analyzed both by counting participants every time they were reported in all papers and by counting the unique number of participants in only the original trials (primary paper published). A total of 132 Pelvic Floor Disorders Network publications were published between 2003 and 2020. Of these, 21 were excluded because they were methods papers or described research without participants. Of the 111 remaining articles, 90 (81%) included descriptions of race and 55 (50%) included descriptions of ethnicity. All 13 primary trials described race and 10 of 13 (76.9%) described ethnicity. Of those publications that described race, 50 of 90 (56%) included only the categories of “White,” “Black,” and “Other,” and 14 of 90 (16%) only described the percentage of White patients. Of the 49,218 subjects, there were 43,058 (87%) with reported race and 27,468 (56%) with reported ethnicity. Among subjects with race and ethnicity reported, 79% were reported as White, 9.9% as Black, 0.4% as Asian, 0.1% as American Indian or Alaska Native, and 4% as “other,” whereas 13% were reported to be of Hispanic ethnicity. The racial and ethnic diversity varied based on the pelvic floor disorder studied (P<.01), which was driven by pregnancy-related and fecal incontinence studies because these had lower proportions of White patients than studies of other pelvic floor disorders. Federally funded Pelvic Floor Disorders Network research does not consistently report the race and ethnicity of participants. Even in the publications that report these characteristics, Black, Indigenous people of color, and people of Hispanic ethnicity are underrepresented. Consistent reporting and recruitment of a diverse population of women is necessary to address this systemic inequity.